Pengelolaan Perdagangan Lintas Batas Dalam Meningkatkan Perekonomian (Melalui Pasar Rakyat Khusus Perbatasan Mota’ain 2017-2019) - Rahma Nur Afifah; Hasna Wijayati; Ganjar Widhiyoga (Peneliti.net, 2023)
This study aims to find out the management of cross-border trade in Motaain in improving the economy with the presence of traditional border-specific folk markets during 2017-2019. The author wrote this study because with the presence of the traditional Motaain market, economic growth and public welfare on the border of Motaain, there is an increase. As well as the construction of PLBN as a cross-border trade route between countries. Indonesia wants to make the border area the front, to realize economic growth, as does the border in Belu, East Nusa Tenggara. The presence of cross-border trade will be able to build up previously unmanaged natural resources and increase human resources. The theme is based on the theory of economic development and microeconomics. The method in this study is qualitative by describing the existing problem formulation with secondary and primary data retrieval. The result is that cross-border trade management can increase economic growth, especially in the East Nusa Tenggara region that borders directly with East Timor, and certainly reduce the unemployment rate. So that the traditional market for interaction between the two regions becomes a good means of facilitating buying and selling. Border areas can continue to increase with proper and well-regulated development and management